Exploring the Components of Digital Identity on Social Networks Sites : Identifier, Post, Profile Photo and Selfie - Reda El Yazidi (European Scientific Journal, ESJ, 2023)
The digital age has ushered in a paradigm shift in self-expression and identity construction, with social network sites (SNSs) serving as vibrant canvases for individuals to shape and project their digital personas. This article delves into the intricate components of digital identity on SNS, focusing on four key elements: identifiers, posts, profile photos, and selfies.User identifiers, which can be real names or pseudonyms, offer the initial gateway to establishing an online presence. The choice of an identifier signifies a conscious decision to reveal or conceal one's true identity, reflecting the growing complexities of identity management in the digital realm.Posts, the textual and visual content shared on SNS, serve as platforms for self-expression, enabling users to convey thoughts, emotions, and beliefs. These posts often undergo text analysis, unveiling the user's personality traits and emotional states, thus contributing to a comprehensive understanding of digital identity.Profile photos, representing users in a visual form, go beyond mere images ; they are semiotic clues of the individual's personality and appeal, with studies demonstrating associations between facial features and personality traits. The selfie, a burgeoning digital phenomenon, provides insights into self-perception and a quest for recognition. Research has shown that selfies often mirror genuine personality traits, shedding light on users' self-esteem and emotional inclinations.This exploration of the components of digital identity in the context of SNS illuminates the complex interplay between user choices, self-expression, and societal interactions in our increasingly interconnected digital world. Understanding these elements is vital for comprehending the multifaceted nature of contemporary digital identities.